LANTUNAN MASA KECIL DALAM â€œLULLABYBIANUâ€ - Mahardika, Komang Wira Adhi (Institut Seni Indonesia Denpasar, 2018)
?Bibi Anu?//Lamun payu luas manjus/Antenge tekekang//Yatnain ngabe masui//Tiyuk puntul//Bawang anggen sasikepan. The folk song which has deep meaning and full of messages is always ringing in the hearts of Balinese children. Moreover, mother's love for her beloved child in simple lyrics and tones in the